Implementasi Pendidikan Agama Islam dalam Menumbuhkan Kepatuhan Hukum di Masyarakat - Khaerul Khaerul; Utary Rustam; Jahara Jahara (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This study investigates the strategic role of Islamic Religious Education (IRE) in fostering legal awareness and law-abiding behavior in Indonesian society, where positive law alone has not been sufficient to prevent widespread legal violations such as corruption and violence. Using a descriptive qualitative approach with library research, the study analyzes primary sources (Qur’an, hadith, classical and contemporary Islamic scholarship) and secondary sources (educational literature, policy documents, and national curricula) to explore how IRE values are internalized through formal, non-formal, and informal education. The analysis highlights that IRE, especially when integrated with Civic Education, strengthens cognitive, affective, and behavioral dimensions by promoting justice, honesty, responsibility, obedience to legitimate authority, and personal piety as religious obligations that align with national legal norms. Furthermore, the roles of teachers and Islamic educational institutions are shown to be crucial in modeling and institutionalizing these values, thereby positioning IRE as an effective preventive instrument against criminal behavior through the cultivation of self-control, accountability before God, and respect for others’ rights. The findings suggest that a well-implemented, value-oriented IRE contributes significantly to the formation of citizens who comply with the law not merely out of fear of sanctions, but based on internalized faith and moral commitment